Joshua S. answered • 08/27/12

Experienced Engineer looking to Educate

Kimberly,

First of all, don't let it get the best of you! Pick it apart in pieces, then it will seem as overwhelming.

1. Parenthesis - (6-3) = **3**. This simplifies your equation to 2^{2} + 3 * **3**^{2}

2. Exponents - 2^{2 }= **4** and 3^{2 }= **9**. This simplifies your equation to **4** + 3 * **9**

3. Multiplication and Division - 3 * 9 = **27**. This simplifies your equation to 4 + **27**

4. Addition and Subtraction - 4 + 27 = 31. There you go!

Hope this helps. I went under the assumption that (6_3) = (6-3).

Ziah T.

no he is wrong wrong girl you did me wrong you did me wrong girl my mood changed when you walked through the door1h

Christine M.

Excellent, Joshua. Simple. Clear.

08/27/12